2019
DOI: 10.1038/s41419-019-1537-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer testis antigen 55 deficiency attenuates colitis-associated colorectal cancer by inhibiting NF-κB signaling

Abstract: Colitis-associated cancer (CAC), a prototype of inflammation-associated cancer, is one of the most common gastrointestinal tumors. As a potential cancer testis antigen (CT antigen), cancer testis antigen 55 (CT55) is expressed in different tumors and normal testes. However, its role in CAC remains unknown. Here, we identified CT55 as a new potent promoter of CAC. We discovered that Ct55 deficiency alleviated inflammatory responses, decreased cell proliferation and colitis-associated tumorigenesis in an azoxyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is highly expressed in HCC and related to the invasive biological behavior of HCC cells, but the specific mechanism is not fully understood ( Pan et al, 2014 ). CT55 is also a member of the cancer testicular antigen family, and studies have found that CT55 deficiency inhibits the NF-KB signaling pathway, thereby attenuating colitis-associated cancers ( Zhao et al, 2019 ). Studies have also shown that CT55 regulates mitochondrial activity and thus maintains the proliferation of cancer cells ( Aurrière et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed in HCC and related to the invasive biological behavior of HCC cells, but the specific mechanism is not fully understood ( Pan et al, 2014 ). CT55 is also a member of the cancer testicular antigen family, and studies have found that CT55 deficiency inhibits the NF-KB signaling pathway, thereby attenuating colitis-associated cancers ( Zhao et al, 2019 ). Studies have also shown that CT55 regulates mitochondrial activity and thus maintains the proliferation of cancer cells ( Aurrière et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer tissues and paired noncancerous tissues were obtained from Tongji Medical College of Huazhong University of Science and Technology in a previous study. 24 None of the patients received chemotherapy prior to colectomy. Written informed consent forms were obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, according to research, CT55 functions as a stimulator of nuclear factor-kB (NF-kB) signaling induced by tumor necrosis factor (TNF)-a by binding to the IkB kinase complex. Deficiency of CT55 suppresses the development of colitis-associated CRC (62).…”
Section: Tumorigenesis Development and Metastasismentioning
confidence: 99%